CULTURE AND IDENTITY OF WOMEN CHARACTERS IN AMITAV GHOSH’S FLOOD OF FIRE - Satya Narayan (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
Amitav Ghosh’s Flood of Fire (2015) is the last volume of the ‘Ibis trilogy’ published in 2015. The novel is set against the First Anglo- Chinese Opium War of 1839-1841. The incidents in the novel move through a meandering zig-zag setting of India, Singapore and China. This novel deals with the lives of all the escapee characters of Ibis and how they find themselves again together grappling with their passions, desires, ambitions, insecurities, sexualities, and destinies. My paper proposes to examine and explore the cultural identity of women characters in Flood of Fire from the perspective of post-colonialism and postmodernism. I would explore cultural and identity situation in Flood of Fire. This novel is basically related to the rise and fall of protagonist characters. In this novel the events are dictated by the condition and movements of people. The perspective of writing will be the loss of homeland, money, national and cultural identity of women characters. By using the tools of deconstruction, this paper would focus on how the characters try to escape their wealth, identity, race, bodies, and places of origin while reconstructing his/her identity. In this I would show how the women characters attempt to reconstruct their cultural and personal identity by achieving success in her life. Keywords: Meandering, homeland, deconstruction andidentity